A case of testicular atrophy associated with cystic fibrosis. (23rd September 2020) - Profka, Eriselda; Rodari, Giulia; Giacchetti, Federico; Berrettini, Alfredo; Manzoni, Gianantonio; Daccò, Valeria; Arosio, Maura; Giavoli, Claudia; Colombo, Carla
Abstract : Summary: An 8-year-old boy with cystic fibrosis came to our attention for an empty scrotum. General physical examination showed a normal penis and hypoplastic scrotum with non-palpable testes bilaterally. Routine blood investigations showed low levels of LH, testosterone, inhibin B and antiMullerian hormone and elevated levels of FSH. Karyotype was normal. An abdominal ultrasound confirmed the absence of the testes into the scrotum, in the inguinal region and abdomen. At laparoscopy were noted bilaterally hypotrophic spermatic vessels, absence of the vas deferens and a closed inner ring. Inguinal exploration found out a small residual testis and histological examination showed fibrotic tissue. This is the first case of testicular atrophy associated to CFTR mutation described. The process that led to bilateral testicular and vas deferens atrophy remains unexplained, a possible influence of CFTR dysfunction cannot be ruled out, although it is possible that these conditions are independently associated. Learning points: Cystic fibrosis produces a multisystemic disease which can affect also the reproductive tract. Nearly 97–98% of male patients are infertile because of congenital bilateral absence of vas deferens. A correlation between cystic fibrosis and bilateral testicular atrophy could be possible.